Human-induced vegetation degradation and response of soil nitrogen storage in typical steppes in Inner Mongolia, China. (January 2016) - Li, X.B.; Li, R.H.; Li, G.Q.; Wang, H.; Li, Z.F.; Li, X.; Hou, X.Y.
Abstract: The residuals trend (RESTREND) method was used to analyze spatial distribution and gradients of vegetation degradation over three time scales: short-term (2006–2011), medium-term (2001–2011), and long-term (1990–2011) and the responses of soil nitrogen storage at different vegetation degradation gradients were compared. The analyses used the 10-day synthetic normalized difference vegetation index of the advanced very high resolution satellite image (1 km 2, 1990–2011) and field surveys of typical steppes of Inner Mongolia, China to compare the responses of soil nitrogen storage at different vegetation degradation gradients. The results showed highly significant regression correlation between the maximum values of the normalized difference vegetation index and the natural logarithm of precipitation on pixel spatial series. Differences in the spatial distribution and gradients of human-induced degradation of vegetation were observed. Soil nitrogen storage decreased as vegetation degradation increased; whereas the impact of vegetation degradation on soil nitrogen decreased as soil depth increased. Thus, the modified RESTREND method can identify vegetation degradation gradients at a regional scale, and the response of soil nitrogen storage can be determined through experimental analysis. Highlights: RESTREND method was modified at calculation the residuals of NDVImax . Vegetation degradation was estimated on three temporal scales. Soil N storage was described at different vegetation degradation gradients. Effect on soil nitrogen storage of vegetation degradation decreases with soil depth.